2015
DOI: 10.1371/journal.pone.0137297
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theoretical Analysis of BOLD Functional Connectivity during Human Sleep without EEG Monitoring

Abstract: BackgroundFunctional brain networks of human have been revealed to have small-world properties by both analyzing electroencephalogram (EEG) and functional magnetic resonance imaging (fMRI) time series.Methods & ResultsIn our study, by using graph theoretical analysis, we attempted to investigate the changes of paralimbic-limbic cortex between wake and sleep states. Ten healthy young people were recruited to our experiment. Data from 2 subjects were excluded for the reason that they had not fallen asleep during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Pulse oximetry is easier to implement and less affected by MR gradient artifact than ECG. While the smooth pulse waveform might offer less precision for peak detection, it has been shown to produce comparable HRV values as ECG (Iyriboz et al, 1991 ) and used to derive HRV values during rs-fMRI (Lv et al, 2015 ; Guo et al, 2016 ). Therefore, pulse oximetry might be used for sleep detection instead of ECG, which could be formally tested in the future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse oximetry is easier to implement and less affected by MR gradient artifact than ECG. While the smooth pulse waveform might offer less precision for peak detection, it has been shown to produce comparable HRV values as ECG (Iyriboz et al, 1991 ) and used to derive HRV values during rs-fMRI (Lv et al, 2015 ; Guo et al, 2016 ). Therefore, pulse oximetry might be used for sleep detection instead of ECG, which could be formally tested in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is hard for subjects to fall asleep with EEG scalp on. Lv et al identified sleep state using HRV derived from peripheral pulse signals, and observed consistent brain network properties compared to those derived from EEG based studies (Lv et al, 2015 ). Moreover, HRV measures are widely used, solely or combined with other physiological signal measures, as features in machine learning models to predict and detect the fatigue and sleepiness of drivers.…”
Section: Introductionmentioning
confidence: 89%
“…In our study, we measured the effective connectivity determined by the Granger causality only at the level of the scalp, which may limit the interpretations of our results. Otherwise, although we only analysed data from a relatively small group of healthy individuals, the samples included in this study were at least similar or even larger than those of most other studies investigating the SWN organization during sleep [2,4,33,55,57,69,75,[82][83][84][85][86][87], which should allow an adequate interpretation of our results. However, in order to confirm the results highlighted in our study, it seems important to carry out replication studies on samples at least similar to those in our study.…”
Section: Limitationsmentioning
confidence: 99%
“…Basic research on different stages of normal sleep is important for understanding sleep function and how sleep affects mental states. Functional connectivity (FC) in human brain networks, which objectively describes the communication between different brain regions, has also been introduced to the field of sleep research [5]- [7]. Some studies have described the FC during normal sleep [8]- [10]; however, they focused on the generalities of overall normal groups and seldom mentioned differences between groups with different characteristics (such as different sex) or among individuals.…”
Section: Introductionmentioning
confidence: 99%